The Original Language of Pseudo-Philo's Liber Antiquitatum Biblicarum - Harrington, Daniel J. (Harvard theological review, 1970)
For all practical purposes, the lengthy and comprehensive essay of Leopold Cohn published in 1898 introduced Pseudo-Philo's Liber Antiquitatum Biblicarum to modern scholars. To demonstrate that the existing Latin text was a translation from the Greek, Cohn listed individual words presumably transliterated from the Greek (metra, holocaustomata, epomis, cataracte, eremus, etc.), noted that many biblical names were written according to their Greek forms (Abel, Enoc, Noe, Jesus, etc.), and pointed out a few LXX readings implying, as he thought, the use of the Greek Bible. However, on the basis of other names, the frequent use of et to join sentences, as well as the occurrence of idioms as et factum est, responderunt dicentes, etc., Cohn concluded that the work must have been originally written in Hebrew. While these considerations may have some indicative force, they do not really prove the point at issue. It is imperative, therefore, that we uncover more decisive proofs for determining the languages in which LAB has been transmitted.